PERMINTAAN KONSUMEN JASA LINGKUNGAN WISATA ALAM MEMPAWAH MANGROVE PARK (MMP) KABUPATEN MEMPAWAH - Rahayuni, Sri; Roslinda, Emi; Muin, Sudirman (JURNAL HUTAN LESTARI, 2019)
Mempawah Mangrove Park (MMP) is an ecotourism in West Kalimantan, especially in Mempawah Regency. MMP besides a tourist attraction is also an area of research and education. Visitors tend to increase every year starting from August 23 2016 – April 27 2017 visitors come from local communities of Mempawah Regency and from outside Mempawah Regency such as Pontianak City, Singkawang City and Kubu Raya. Factors that influence the demand for MMP Mangrove nature tourism consumers are attractiveness, travel costs, time, and income. The research aims to measure the demand of consumers of Mempawah District MMP natural tourism services, and examine the factors that influence the demand for consumers of MMP natural tourism services. The sample used in this study were 45 respondents who visited MMP using the Accidental Sampling method. The analytical method in this study is descriptive analysis, basic assumption test, classic test, and multiple linear analysis. Descriptive analysis result of the demand consumers of MMP natural tourism services indicate that consumer demand is said to be high. The results of 45 respondents in this study were 22 respondents (48.89%) visited 3 times in the last 1 year. The results of the study used the basic assumption test, classic assumption test and multiple linear regression. The results of multiple linear regression analysis show that attraction variables have a positive and significant effect on the demand of consumers of MMP natural tourism services. Travel and time cost variables show a negative and insignificant influence on the demand of consumers of MMP natural tourism services because most of the visitors are local people of Mempawah Regency who do not require a high enough travel cost and a long time. The income variable shows a negative and significant effect on the demand of consumers of MMP natural tourism services. This happens to income still in the low category because most MMP visitors are status young as students who do not have a steady income.Keywords: Attractiveness, Consumer Demand, Income, MMP, Time and Travel Cost.